Effect of Cranberry Fruit Extract (Vaccinium Macrocarpon) on Vegf Value in Wistar (Rattus Norvegicus) Mouse Pyelonephritis Model - Desika Aura Putri; Muhammad Andriady Saidi Nasution; Andre Budi; Adrian Joshua Velaro (International Journal Labs, 2025)
This study aimed to investigate the effect of cranberry extract on Vascular Endothelial Growth Factor (VEGF) levels and renal histopathological improvement in a rat model of pyelonephritis. Seven treatment groups were used, including a sham group, a negative control, a positive control (ciprofloxacin), and cranberry extract groups at doses of 100, 200, 300, and 400 mg/kgBW. Data were analyzed using the Kruskal–Wallis test followed by an all-pairwise comparison. The results showed a significant difference in VEGF levels among the groups (p = 0.046), with notably higher VEGF expression in the 300 mg/kgBW and 400 mg/kgBW cranberry groups compared to the negative control. Histopathological analysis revealed reduced inflammatory cell infiltration and improved tubular structure in the high-dose cranberry groups. These effects are associated with the bioactive compounds of cranberry, particularly proanthocyanidins and flavonoids, which exhibit anti-inflammatory, antioxidant, and angiogenic activities by enhancing VEGF expression. In conclusion, cranberry extract at doses of 300 mg/kgBW and 400 mg/kgBW demonstrates strong potential as a natural nephroprotective agent that accelerates renal tissue healing in pyelonephritis. These findings support the use of cranberry extract as an adjuvant therapy to complement conventional treatment for urinary tract infections